1996
DOI: 10.1016/0895-7061(96)00058-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between birth weight and awake blood pressure in children and adolescents in absence of intrauterine growth retardation

Abstract: This study was designed to examine the relationship between birth weight (BW) and ambulatory blood pressure in children and adolescents, born at term in absence of intrauterine growth retardation. Twenty-four hour ambulatory blood pressure monitoring (ABPM) was performed on 332 children (150 boys), aged from 6 to 16 years. Subjects were stratified by BW tertiles and age. ABPM was performed using SpaceLabs 90207 monitor during a regular school day. Blood pressure (BP) was measured every 20 min from 06:00 to 24:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…22 Although remaining controversial, a weight of evidence exists to suggest a negative association between birth weight and blood pressure in later life. [5][6][7] Similarly, evidence exists for such a relationship in children, [10][11][12] although a previous study of this cohort suggested that the relationship may vary with age and gender. 13 Much less is known regarding the possibility that pulse pressure may be in part determined by fetal growth.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…22 Although remaining controversial, a weight of evidence exists to suggest a negative association between birth weight and blood pressure in later life. [5][6][7] Similarly, evidence exists for such a relationship in children, [10][11][12] although a previous study of this cohort suggested that the relationship may vary with age and gender. 13 Much less is known regarding the possibility that pulse pressure may be in part determined by fetal growth.…”
Section: Discussionmentioning
confidence: 85%
“…[9][10][11] Less is known regarding the potential link between birth weight and pulse pressure, although a recent study reported a negative association. 13 What this study adds K We found a significant negative association between birth weight and pulse pressure, although this association was restricted to the girls in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] It has been estimated that a 1 kg higher birth weight is typically associated with a 2-4 mm Hg lower systolic blood pressure. 7 Evidence also exists for such a relationship in childhood, [8][9][10][11] but it has been suggested to vary with age and gender. 12 Fewer studies have addressed the contribution of length of gestation at birth in determining risk of adverse health in later life.…”
Section: Introductionmentioning
confidence: 99%
“…Results from recent studies of ambulatory BP in children include observations of an inverse association of birth weight with daytime SBP in children born from full-term pregnancies 16 and an inverse association of birth weight with mean 24-h SBP in a sample where no association of birth weight with office BP was found. 17,18 In our current study, we investigated the association of size at birth with hypertensive status defined by both office BP measured at a clinic and 24-h ambulatory BP monitoring in 70-year-old men.…”
Section: Introductionmentioning
confidence: 99%